(untitled) (Research, Society and Development, 2022)
The objective of the present study was to evaluate the knowledge of medical students about human papillomavirus (HPV) infection, in addition to addressing knowledge about prevention and the rate of vaccine adepts. Cross-sectional study, through the application of an online questionnaire, which addressed the following aspects: technical and practical knowledge about HPV and its prophylaxis; vaccination rate of academics. The respective study had the participation of 139 medical students, 74.9% (n=103) were female and 25.9% (n=36) were male. In comparison between the sexes, women showed a greater participation to gynecology offices, as well as the discussion about STIs (p<0.001). Females were more likely to receive the vaccine through family members (p<0.01). As well as receiving at least 1 dose (p<0.001) and performing a complete vaccination schedule (p<0.001), compared to females. Academics aged 25 years or older answered the theoretical questions of the questionnaire more correctly (p=0.01), being less vaccinated (p=0.03), when compared to younger academics (between 18 and 24 years). Internship students showed greater knowledge about vaccine efficacy (p=0.01) in relation to the basic and clinical cycle. The university students showed excellent theoretical and practical knowledge about infection and prophylaxis. Finally, most vaccinated academics received a total of three doses.